Stunting Prevalence, Plasma Zinc Concentrations, and Dietary Zinc Intakes in a Nationally Representative Sample Suggest a High Risk of Zinc Deficiency among Women and Young Children in Cameroon. Issue 3 (31st December 2013) - Engle-Stone, Reina; Ndjebayi, Alex O.; Nankap, Martin; Killilea, David W.; Brown, Kenneth H.
Abstract: Before initiating a mass zinc fortification program, this study assessed the prevalence of and risk factors for low zinc status among Cameroonian women and children. In a nationally representative survey, we randomly selected 30 clusters in each of 3 strata (North, South, and Yaoundé/Douala) and 10 households per cluster, each with a woman aged 15–49 y and a child aged 12–59 mo ( n = 1002 households). Twenty-four-hour dietary recalls (with duplicates in a subset) and anthropometric measurements were conducted, and non-fasting blood was collected to measure plasma zinc concentration (PZC) and markers of inflammation. PZC was adjusted for methodologic factors (time of collection and processing, and presence of inflammation). The prevalence of stunting was 33% (32% South; 46% North; 13% Yaoundé/Douala). Among women, 82% had low adjusted PZC (<50 μ g/dL for pregnant women; <66 μ g/dL for others; 79% South, 89% North, 76% Yaoundé/Douala). Among children, 83% had low adjusted PZC (<65 μ g/dL; 80% South, 92% North, 74% Yaoundé/Douala). Risk factors for low PZC among women and children and for low height-for-age Z-score among children were similar and included residence in the North region and rural areas and households with low socioeconomic status. Using estimated average requirement values from the International Zinc Nutrition Consultative Group (IZiNCG), 29 and 41% of women had inadequate zinc intakes, assuming moderate and low bioavailability, respectively, but only 8% of children had inadequate zinc intake. Depending on the estimated physiologic zinc requirement applied, 17% (IZiNCG) and 92% (Institute of Medicine) of women had inadequate absorbable zinc intakes. Total zinc intakes were greatest in the North region, possibly because of different dietary patterns in this area. Zinc deficiency is a public health problem among women and children in Cameroon, although PZC and dietary zinc yield different estimates of the prevalence of deficiency. Large-scale programs to improve zinc nutrition, including food fortification, are needed.